Haemosporidian prevalence, parasitaemia and aggregation in relation to avian assemblage life history traits at different elevations. Issue 5 (April 2021) - Rodríguez-Hernández, Karla; Álvarez-Mendizábal, Paulina; Chapa-Vargas, Leonardo; Escobar, Federico; González-García, Fernando; Santiago-Alarcon, Diego
Graphical abstract: Highlights: Haemosporidian prevalence increased with elevation. Prevalence of Plasmodium was higher at lower elevations. Prevalence and parasitaemia of Haemoproteus and Leucocytozoon increased with elevation. Haemosporidian parasitaemia was lower in solitary birds than those in a pair or engaging in gregarious behavior. Haemosporidian aggregation decreased with elevation. Abstract: The transmission of vector-borne protozoa such as parasites of the Order Haemosporida is dependent on both biotic and abiotic factors such as host life history traits and environmental conditions. This study aimed to identify the variables that determine haemosporidian prevalence, parasitaemia and aggregation within the context of elevation and avian life history traits in Central Veracruz, Mexico. We sampled 607 birds from 88 species; we used microscopy and the mtDNA cytochrome b gene to detect parasites. We found an overall prevalence of 32.3%. Haemosporidian prevalence was 21.6% in tropical sub-deciduous forest (at sea level), 38% in tropical deciduous forest (265 m above sea level (asl)), 19.4% in montane cloud forest (1630 m asl), and 51.7% in pine-oak forest (2790 m asl). The prevalence of each parasite genus was strongly influenced by elevation (a proxy of habitat type). Plasmodium showed the highest prevalence at low elevation. Haemoproteus increased in prevalence with elevation. Leucocytozoon displayed the highest prevalence at the highest elevation (pine-oak forest). Haemoproteus spp. and Leucocytozoon spp. prevalences were higher in open cup than in closed nests. Haemoproteus prevalence and haemosporidian parasitaemia were lower in solitary birds than birds with pairing and gregarious behavior. Haemosporidian aggregation decreased with elevation, yielding the significantly lowest values at the pine-oak forest. Elevation distribution patterns of prevalence for each genus were similar to those previously reported in other geographical areas (e.g., South America, Europe).